Inferior myocardial wall ischemia on SPECT-MPI in patients with non dominant right coronary artery and non significant coronary artery disease. (1st July 2022) - Mplani, Virginia; Apostolopoulos, Dimitrios; Koufou, Eleni; Spyridonidis, Trifon; Tsigkas, Grigorios; Hahalis, George; Alexopoulos, Dimitrios; Davlouros, Periklis
Abstract: Background: The impact of a non-dominant right coronary artery (NDRCA), on single photon emission computed tomography (SPECT) myocardial perfusion imaging (MPI)has not been clarified. Methods and results: We compared SPECT-MPI results of consecutive patients without significant (diameter stenosis ≥50%)coronary artery disease (CAD) and a NDRCA (Group-1), with those of patients from our database without CAD and a dominant RCA (Group-2). All patients were subjected to SPECT-MPI with I.V. infusion of adenosine, and TC 99 -tetrofosmin. Group-1 included 69 patients (55 men, 79.7%), mean age 66.8 ± 9.8 years. Group-2 consisted of 79 patients (56 men, 70.9%), mean age 62.7 ± 11.5. There was no difference in demographics and CAD risk factors between the two groups. The SPECT-MPI revealed inferior wall ischemia, in 35 patients (50.7%), in Group-1 and 27 patients (34.1%), in Group-2 ( P  = 0.041). Conclusions: A relatively high rate of reversible SPECT-MPI perfusion defects may be anticipated in patients with an unobstructed NDRCA compared to patients with a dominant RCA. Highlights: A non-dominant right coronary artery (NDRCA) is found in approximately 7–9% of the general population. Its impact –if any- on single photon emission computed tomography (SPECT) myocardial perfusion imaging (MPI), has not been studied prospectively. We compared SPECT-MPI results between 69 consecutive patients without significant, coronary artery disease (CAD) and 79 patients with a dominant-RCA, also without significant CAD. There was no difference in demographics between the two groups. The SPECT-MPI revealed ischemia in 50.7%, patients with NDRCA and 34.2%, in patients with a dominant RCA, P  = 0.041. The semiquantitive segmental analysis of radiotracer uptake in the inferior wall revealed that the difference between the perfusion score at stress and rest (SDS), was significantly higher (1.25 ± 1.45 vs. 0.77 ± 1.08, P  = 0.028), in patients with NDRCA compared to the rest. In summary this study shows that a relatively high rate of reversible SPECT-MPI perfusion defects may be anticipated in patients with an unobstructed NDRCA compared to patients with a dominant RCA.